Periods of Migration Waves and Social Demography of Bosnian Population in Germany - Yusuf Adıgüzel; Damir Softic (Medya ve Kültür)
As seen in the case of Bosnia, there are many difficulties in studying the population living abroad. Discussions that started with unclear data on Bosnian society are going on in isolation from each other. A reliable database is needed to develop a realistic and effective program on the Bosnian population in Germany. However, information on firstgeneration immigrants and subsequent generations is often incomplete and far from reliable enough. Based on German official government statistics, this article focuses on the migration processes and current demographic structure of the Bosnian-Herzegovinian community in the country. According to the data of the German Federal Bureau of Statistics (Statistisches Bundesamt), 289 thousand people have immigration experience or consist of first-generation people, and this number reaches 415,000 with the new generation immigrants descended from them. Nearly half of the population of Bosnian origin in Germany participated in the migration process through family reunification and marriage. 84% of the immigrant population is concentrated in 4 of the 16 states in Germany. Compared to other immigrants in the country, Bosnian society, which has a better level of socioeconomic indicators such as education, employment and income level, is experiencing a successful integration process with the host society.